Rural perspective about anesthesia and anesthesiologist: A cross-sectional study - P M Singh; Anil Kumar; Anjan Trikha (Wolters Kluwer Medknow Publications, 2013)
Background: More than 3/4 th of Indian population resides in rural areas. The public awareness towards "Anesthesia and Anesthesiologist" is limited even in urban population. There is no data available from rural India on this perspective. Our cross-sectional analysis highlights this lack of public awareness and discusses possible remedies to overcome these limitations. Materials and Methods: Surgical outpatient department of Comprehensive Rural Health Center (CRHC) Ballabgarh, Haryana (model CRHC for Indian health schemes) was screened for 6 months period. A questionnaire divided into 3 parts (Awareness about Anesthesiologist, Consent, Present surgical experience) was filled out for each patient. The patients on the basis of their answers were classified as "aware or unaware," also source of patient information was analyzed. Results: Even with an extremely low threshold, only 36.44% of population could be classified as aware, and commonest source of their information was not anesthesiologist but surgeon (64.32%). 83.6% patients were not aware of contents of pre-operative consent they had signed and further, only 3.4% were aware of anesthesia-related issues. Pain was reported as the most common pre-operative fear and post-operative patient concern. 47.17% patients due to lack of pre-operative counseling were not able to recognize the type of anesthesia and thought they had received both general anesthesia and spinal anesthesia. At the end, after explaining the role of anesthesia for surgery, 99.06% patients presented desire to meet the anesthesiologist beforehand if they were to be operated in future. Conclusion: The rural awareness about anesthesia is extremely low likely because of low literacy rates and lack of pre-operative counseling by anesthesiologist. Both patient and anesthesiologist must understand the importance of consent, as it is not only a legal binding but can eliminate pre-operative factitious fears of patients and can improve patient satisfaction towards surgery.